Ответы и объяснения

Лучший Ответ!
  • Участник Знаний
2014-04-03T21:18:53+04:00
Б)
2X^2 + X - 1 = ( X + 1)*( 3X + 1 ) 
2X^2 + X - 1 = 3X^2 + 4X + 1 
3X^2 - 2X^2 + 4X - X + 1 + 1 = 0 
X^2 + 3X + 2 = 0 
D = 9 - 4*1*2 = 1
V D = 1 
X1 = ( - 3 + 1 ) : 2 = ( - 1 ) 
X2 = ( - 4 ) : 2 = ( - 2 ) 
Ответ ( -1) и ( - 2 )
----------------------------------------
B) 
X * ( X - 2 ) = X^2 - 2X ( знаменатели, они равны между собой) 
-----------------
( 3Х + 1)*( X - 2) + 5X = 6X - 2 
3X^2 - 6X + X - 2 + 5X = 6X - 2 
3X^2 - 5X + 5X - 2 = 6X - 2 
3X^2 - 2 - 6X + 2 = 0 
3X^2 = 6X 
3X = 6 
X = 2
-------------------
Х * ( X - 2 ) > 0 
X > 0 
X - 2 > 0 ---> X > 2 
----------------
Ответ Нет решений